Quantifying feed intake and feeding intensity using two experimental conditions and the effect of different feeding strategies on the production parameters of farmed South African abalone, haliotis midae - Wortley, Ross Michael (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science)
As abalone are slow-growing animals there is a high investment of capital, running costs and labour in commercial abalone farming. Revenue needs to be maximised by achieving fast growth rates. A foremost driver of abalone growth is feed intake and feeding intensity of the abalone as well as the feeding regimen a farm utilises. While feed intake is well-documented in H. midae, there is a paucity of information regarding this aspect in abalone above 70 g and the relationship between feeding intensity, feed conversion rate (FCR) and daily growth rate needs to be documented. Similarly, there are a limited number of studies dealing with the effects of different pellet types of the same formulation, that differ only in shape and size, on feed intake and production in H. midae. This study made use of both a controlled laboratory experiment and commercial-scale farm experiment with the aim of testing whether feed intake information produced under laboratory conditions can provide good estimates of feed intake under farming conditions, which can further be implemented into feeding strategies on abalone farms. This study quantified daily feed intake (F) in 10 "“ 20 g, 100 "“ 110 g and 150 "“ 160 g abalone weight classes using two different pellet types and determined the relationship between the duration of feed availability and feed intake under laboratory conditions. The effect of three different pellet type strategies (fed daily: a leaf-only strategy = L d-1, a short-pellet only strategy = SP d-1, and a strategy that used both = B d-1) on abalone production parameters under farming conditions such as growth rate, feed conversion ratio (FCR), feeding intensity (FI) and weight variation of 30 "“ 40 g H. midae was also investigated. A commercial-scale farm study was designed to test the effect of four commercially relevant feeding regimens (three size-specific regimens and one commercially practiced feeding method) on the growth, FCR, feeding intensity and weight variation of these three abalone weight classes while taking into account an economic model to assess the profitability of each feeding regimen. Daily feed intake as a percentage of body mass (% BM d-1) was a function of abalone weight class between the 10 "“ 20 g and two larger weight classes 100 "“ 110 g and 150 "“ 160 g p < 0.0001), however feed intake was not different between the 100 "“ 110 g and 150 "“ 160 g weight classes. Pellet type did not affect feed intake in all abalone weight classes (p = 0.15). Feed intake (F) was positively linearly correlated with duration of feed availability (h) in the 10 "“ 20 g weight class (r2 = 0.76, p <0.00001) and logarithmically correlated in the 100 "“ 110 g (r2 = 0.25, p < 0.02) and 150 "“ 160 g (r2 = 0.52, p < 0.0001) weight classes (10 "“ 20 g abalone-1: 3 F (% BM) = 0.02(h) + 0.1976, 100 "“ 110 g abalone-1: F (% BM) = log10(h)*0.17 + 0.17, 150 "“ 160 g abalone-1: F (% BM) = log10(h)*0.36 + 0.07). There was no significant difference in monthly average abalone weight, daily growth rate (G), FCR and feeding intensity between each pellet type strategy (G: p = 0.60, FCR: p = 0.62, FI: p = 0.54 ). However, abalone grew well over the 112-day growth period with average abalone weight increasing significantly between each monthly sample time (pooled pellet type strategy: Huynh-Feldt correction; p < 0.00001). Furthermore, abalone fed the leaf-only pellet type strategy (L d-1) fell into higher weight classes after a 112-day growth period (Z test: 50 "“ 70 g: 72%) which was 16.1 % higher compared to the SP d-1 and B d-1 strategies. Daily growth rate (r2 = 0.34, p < 0.01) and FCR (r2 = 0.42, p < 0.004) was negatively correlated and FCR was positively correlated with daily feeding intensity, respectively (G = - 2.59 (FI) + 1.526, FCR = 8.8082 (FI) "“ 2.7108). Feeding regimen affected the production parameters of three abalone weight classes. The method practiced on the farm resulted in the best growth in the 10 "“ 20 g abalone weight class. The farm feeding method resulted in slower yet more efficient growth rates (lowest FCR values) in the abalone weight classes, 100 "“ 110 g and 150 "“ 160 g abalone- 1. However, size-specific feeding regimens resulted in the fastest growth rates but resulted in higher FCR values (less efficient). The relationship between feeding intensity, daily growth rate and FCR all showed that an increase in feeding intensity results in increased daily growth rates and FCR values. The economic model suggests that the higher FCR values associated with size-specific regimens, which have higher associated costs to producing abalone, were greatly outweighed by the growth attained by the abalone in the 100 "“ 110 g and 150 "“ 160 g weight classes. The size-specific regimens generated a higher potential monetary value of abalone after a 112-day period, which would consequently result in higher income for abalone farms. For abalone ranging from 100 "“ 110 and 150 "“ 160 grams, the economic model suggested that in a quarterly grading schedule (112 days) that abalone be fed the size specific daily rations, which is a function of body mass, at 0.35 % BM d-1 and 0.352 % BM d-1, respectively. The two experimental conditions used in this study produced feed intake and production parameter information that is beneficial to South African abalone farmers. The small-scale laboratory study produced information on feed intake that can be used as reference values as to what abalone in these weight classes can consume on a daily basis. The laboratory study can provide estimates of feed intake under farming conditions but should only be used as minimum 4 values when determining size-specific feeding regimens. To maximise abalone growth, farmers should utilise size-specific feeding regimens for abalone above 30 g. Daily growth rate and FCR can be predicted as a function of the abalone's feeding intensity. Further studies are needed to determine the effects of abalone weight class on production parameters when testing different pellet types as well as an exploration into behavioural studies focusing on diet preferences. Additionally, future studies need to take into consideration abalone above the weight of 100 g with additional focus of research on behavioural, genetic and environmental aspects on abalone feed intake.
Keywords: Mariculture -- South Africa; Abalone culture; Abalones Growth; Abalones Feeding and feeds; Feed conversion ratio; Haliotis midae